Mechanical behavior of a sandwich with corrugated GRP core: numerical modeling and experimental validation (Fracture and Structural Integrity, 2014)
In this work the mechanical behaviour of a core reinforced composite sandwich structure isstudied. The sandwich employs a Glass Reinforced Polymer (GRP) orthotropic material for both the twoexternal skins and the inner core web. In particular, the core is designed in order to cooperate with the GRPskins in membrane and flexural properties by means of the addition of a corrugated laminate into the foamcore. An analytical model has been developed to replace a unit cell of this structure with an orthotropicequivalent thick plate that reproduces the in plane and out of plane behaviour of the original geometry.Different validation procedures have been implemented to verify the quality of the proposed method. At first acomparison has been performed between the analytical model and the original unit cell modelled with a FiniteElement mesh. Elementary loading conditions are reproduced and results are compared. Once the reliability ofthe analytical model was assessed, this homogenised model was implemented within the formulation of a shellfinite element. The goal of this step is to simplify the FE analysis of complex structures made of corrugatedcore sandwiches; in fact, by using the homogenised element, the global response of a real structure can beinvestigated only with the discretization of its mid-surface. Advantages are mainly in terms of time to solutionsaving and CAD modelling simplification. Last step is then the comparison between this FE model andexperiments made on sandwich beams and panels whose skins and corrugated cores are made of orthotropiccross-ply GRP laminates. Good agreement between experimental and numerical results confirms the validity ofthe proposed model.
Keywords: Sandwich Structures